Interim (18F)FDG PET/CT can predict response to anti-PD-1 treatment in metastatic melanoma - Sachpekidis, Christos; Kopp-Schneider, Annette; Pan, Leyun; Papamichail, Dimitrios; Haberkorn, Uwe; Hassel, Jessica C.; Dimitrakopoulou-Strauss, Antonia (European journal of nuclear medicine and molecular imaging, 2021)
In an attempt to identify biomarkers that can reliably predict long-term outcomes to immunotherapy in metastatic melanoma, we investigated the prognostic role of [18F]FDG PET/CT, performed at baseline and early during the course of anti-PD-1 treatment.
Published online: 18 December 2020
Im Titel steht der Ausdruck (18 F) in eckiger Klammer, "18" ist dabei hochgestellt
Gesehen am 11.01.2024